Numerical simulation of wind loads using computational fluid dynamics on solar panels in Melchor Hall, UP Diliman - Pacer, Jihan S.
Solar panels are lightweight structures used to utilize solar energy as a renewable energy source. Since they are lightweight structures, wind loading is the prevailing criteria for its structural design. However, building codes do not provide design specifications on such loading resulting in the need to develop consistent criteria in evaluating the structural adequacy of the solar panels. This study aims to determine the wind loads acting on solar panels and its effect on the structural condition of the roof of Melchor Hall. Wind flow around Melchor Hall was simulated using computational fluid dynamics. To evaluate the effects of solar panels, wind pressure coefficients on roof surfaces were determined for both building with and without solar panels and then compared. Moreover, contour maps of pressure coefficient distribution were generated to provide visual comparison. Pressure coefficients were also generated on solar panel surfaces and critical resultant forces acting on solar panels were obtained from these results. Design of solar panel orientation was also done through variation of tilt angle by increments of 5°, 10° and 15° relative to the roof inclination and roof-panel distance which ranges from 0.1-0.3 m. It was determined that for the west wing, the existing layout of the solar panels is the most preferred solar panel orientation and for east wing, a roof-panel distance of 0.3 m with 0° tilt angle increment is the most preferred. Additionally, failure analysis on solar panels and anchorage was done. Results showed that anchorage failure is likely to happen in existing layout on the west wing and no failure in the most preferred and existing alyout on the east wing in the event of a typho